Hooking Intermediate-level Students on Literature: Reading La Maison de Claudine with La Maison de Colette - Tama L. Engelking (Studies in 20th & 21st Century Literature, 2026)
Intermediate-level university students studying a foreign language (FL) often find the jump from language classes to literature too difficult and see reading literary texts as irrelevant to their career goals. The Modern Language Association recommends reconfiguring the two-tiered organization of departments, where instruction in language is separate from “content” courses, by integrating the teaching of literature and language at all levels of FL curricula. An appropriately scaffolded and student-centered approach that makes reading literature accessible and more personally meaningful can hook lower-level students and help retain them in our flagging FL programs. This essay reviews the place of literature in FL pedagogy and describes an intermediate-level French lesson that incorporates best practices for bridging the language-literature divide and personalizing reading. It uses multimedia resources associated with La Maison de Colette—a writer’s house museum—to teach a chapter from Colette’s 1922 autobiographical narrative, La maison de Claudine. Students “virtually” walk in Colette’s footsteps, reflect on their own childhoods, and engage in a “creative personalization” storytelling assignment that uses Colette’s text as a model.
Keywords: Sidonie Gabrielle Colette; La maison de Claudine; writer’s house museum; La Maison de Colette; integrated foreign language curriculum; Second Language Acquisition; MLA recommendations; language-literature divide; student-centered approach